Role of solvent molecules as a trigger for the crystal phase transition of syndiotactic polystyrene/solvent complex - Gowd, E. Bhoje; Tashiro, Kohji; Ramesh, C. (Macromolecules, 2008)
The phase transitions occurring in the syndiotactic polystyrene-norbornadiene complex were investigated by simultaneous measurements of wide-angle X-ray diffraction (WAXD) and differential scanning calorimetry (DSC). To understand the effect of norbornadiene molecules on the phase-transition behavior, the delta form samples with different contents of norbornadiene were prepared. By heating these samples, we found that the delta-to-gamma transition occurred well below 100 degrees C in a broad temperature range, and the onset of the transition temperature depended on the content of norbornadiene included in the starting sample. The sample without norbornadiene molecules showed the delta-to-gamma transition to be above 100 degrees C. Upon further heating, the gamma form transformed into a mixture of alpha and beta forms in the presence of norbornadiene molecules, whereas the sample without norbornadiene transformed into only the alpha form. In this way, it has been found that the solvent molecules, which are not completely evaporated from the sample but are transiently trapped in the amorphous region because of the slow diffusion, have a significant role in facilitating the phase transitions as well as the transition temperatures in the crystalline region. On the basis of WAXD and DSC results, a phase-transition model has been reasonably constructed.

Structural phase transitions of syndiotactic polystyrene - Gowd, E. Bhoje; Tashiro, Kohji; Ramesh, C. (Progress in Polymer Science, 2009)
Syndiotactic polystyrene (sPS) exhibits four crystal modifications (alpha, beta, gamma, and delta), along with intermediate forms with different molecular conformations, as well as different chain-packing structures. The extensive literature on the crystal structures exhibited by sPS is reviewed herein, including, the mechanisms of phenomena such as solvent-induced crystallization, thermally induced crystallization and gelation, and the phase transitions among the various crystalline forms. The latter have been studied by static and dynamic wide-angle and small-angle X-ray scattering, infrared and Raman spectra, and neutron scattering, etc., in addition to computer simulations. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: crystal structure; Gelation; phase transition; polymorphism; Solvent-induced crystallization; Syndiotactic polystyrene

Dual nanomechanics in anisotropic porous covalent organic framework janus-type thin films - Mohata, Shibani; Dey, Kaushik; Bhunia, Surojit; Thomas, Neethu; Gowd, E. Bhoje; Ajithkumar, Thalasseril G.; Reddy, C. Malla; Banerjee, Rahul (Journal of the American Chemical Society, 2022)
Empowered by crystalline ordered structures and homogeneous fabrication techniques, covalent organic frameworks (COFs) have been realized with uniform morphologies and isotropic properties. However, such homogeneity often hinders various surface-dependent properties observed in asymmetric nanostructures. The challenge remains to induce heterogeneity in COFs by creating an asymmetric superstructure such as a Janus thin film. In this regard, we propose a versatile yet straightforward interfacial layer-grafting strategy to fabricate free-standing Janus-type COF-graphene thin films. Herein, two-dimensional graphene sheets were utilized as the suitable grafter due to the possibility of noncovalent interactions between the layers. The versatility of the approach was demonstrated by fabricating two distinct Janus-type films, with the COF surface interwoven with nanofibers and nanospheres. The Janus-type films showcase opposing surface morphologies originating from graphene sheets and COF nanofibers or nanospheres, preserving the porosity (552-600 m(2) g(-1)). The unique surface chemistries of the constituent layers further endow the films with orthogonal mechanical properties, as confirmed by the nanoindentation technique. Interestingly, the graphene sheets favor the Janus-type assembly of COF nanofibers over the nanospheres. This is reflected in the better nanomechanical properties of COFfiber-graphene films (E-gra(phene) = 300-1200 MPa; E-COF( )= 15-60 MPa) compared to the COFsphere-graphene films (E-gra(phe)ne = 11-14 MPa; E-CO(F )= 2-5 MPa). These results indicate a direct relationship between the mechanical properties and homo/heterogeneity of Janus-type COF films.

Hierarchical covalent organic framework-foam for multi-enzyme tandem catalysis - Paul, Satyadip; Gupta, Mani; Dey, Kaushik; Mahato, Ashok Kumar; Bag, Saikat; Torris, Arun; Gowd, E. Bhoje; Sajid, Hasnain; Addicoat, Matthew A.; Datta, Supratim; Banerjee, Rahul (Chemical Science, 2023)
Covalent organic frameworks (COFs) are ideal host matrices for biomolecule immobilization and biocatalysis due to their high porosity, various functionalities, and structural robustness. However, the porosity of COFs is limited to the micropore dimension, which restricts the immobilization of enzymes with large volumes and obstructs substrate flow during enzyme catalysis. A hierarchical 3D nanostructure possessing micro-, meso-, and macroporosity could be a beneficial host matrix for such enzyme catalysis. In this study, we employed an in situ CO2 gas effervescence technique to induce disordered macropores in the ordered 2D COF nanostructure, synthesizing hierarchical TpAzo COF-foam. The resulting TpAzo foam matrix facilitates the immobilization of multiple enzymes with higher immobilization efficiency (approximately 1.5 to 4-fold) than the COF. The immobilized cellulolytic enzymes, namely beta-glucosidase (BGL), cellobiohydrolase (CBH), and endoglucanase (EG), remain active inside the TpAzo foam. The immobilized BGL exhibited activity in organic solvents and stability at room temperature (25 degrees C). The enzyme-immobilized TpAzo foam exhibited significant activity towards the hydrolysis of p-nitrophenyl-beta-d-glucopyranoside (BGL@TpAzo-foam: K-m and V-max = 23.5 +/- 3.5 mM and 497.7 +/- 28.0 mu M min(-1)) and carboxymethylcellulose (CBH@TpAzo-foam: K-m and V-max = 18.3 +/- 4.0 mg mL(-1) and 85.2 +/- 9.6 mu M min(-1) and EG@TpAzo-foam: K-m and V-max = 13.2 +/- 2.0 mg mL(-1) and 102.2 +/- 7.1 mu M min(-1)). Subsequently, the multi-enzyme immobilized TpAzo foams were utilized to perform a one-pot tandem conversion from carboxymethylcellulose (CMC) to glucose with high recyclability (10 cycles). This work opens up the possibility of synthesizing enzymes immobilized in TpAzo foam for tandem catalysis.

Eco-friendly gradient porous poly(3-hydroxybutyrate)/natural fiber aerogels for highly efficient thermo-acoustic insulation - Akhila, N. S.; Shrishti, S. K.; Suresh, Sruthi; Torris, Arun; Gowd, E. Bhoje (ACS Applied Polymer Materials, 2026)
The urgent demand for lightweight thermo-acoustic insulation (TAI) materials in transportation and building infrastructure is constrained by difficulties in synthesis and environmental concerns about nondegradable materials. In this study, a strategy is proposed to create gradient porous, biodegradable, fibrillar aerogels via layer-by-layer casting with poly(3-hydroxybutyrate) (PHB), banana fibers (BF), and cellulose nanofibers (CNFs), followed by unidirectional freezing and freeze-drying. These gradient porous aerogels possess a hierarchical porous structure, ensuring excellent hydrophobicity, mechanical strength, and thermal dimensional stability, and exhibit excellent acoustic insulation performance due to impedance mismatch and pore-neck resonance effects, achieving a noise reduction coefficient (NRC) of 0.60. The gradient-structure-based aerogels also exhibit better thermal insulation performance, with ultralow thermal conductivities as low as 0.03 W/(m & centerdot;K). The flame-retardant properties are significantly enhanced by incorporating Al(OH)3 via a solvent-exchange method, thereby achieving a limiting oxygen index (LOI) of 29.3%. The lightweight, gradient-structure-based, biodegradable aerogels possess excellent thermo-acoustic insulation and flame-retardant properties, thereby offering great promise as sustainable insulation materials for next-generation building infrastructure.
Keywords: acousticinsulation; aerogels; biodegradable; flame retardancy; Hydrophobic; poly(3-hydroxybutyrate); Thermal insulation